Sustainable financing for biodiversity conservation: A review of experiences in German development cooperation - Augustin Berghöfer; Lucy Emerton; Alonso Moreno Diaz; Julian Rode; Christoph Schröter-Schlaack; Heidi Wittmer; Hugo van Zyl (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
The financial resources needed for globally implementing the Aichi Biodiversity Targets have been estimated at US 150-440 billion per year (CBD COP11, 2012) - of which only a fraction is currently available. Significant efforts have been undertaken in many countries to increase funding for biodiversity conservation. Nonetheless, this funding shortage remains immense, acute and chronic. However, we do not lose biodiversity and ecosystems primarily for lack of conservation funding but also due to poor governance, wrong policies, perverse incentives and other factors. This begs the question: How should limited conservation resources be used? For directly tackling biodiversity threats, for addressing the underlying drivers, or rather for strengthening the financial management and fundraising capacity of implementing organisations? As country contexts differ, so do the answers. This report synthesizes experiences of German development cooperation working towards improved biodiversity finance in eight countries: Viet Nam, Namibia, Tanzania, Cameroon, Madagascar, Mauritania, Ecuador and Peru. Our findings suggest a shift in perspective in the international biodiversity financing debate: We need to move from a focus on innovative financing mechanisms towards thinking "innovation" more broadly. Financial resource mobilisation needs to go hand in hand with efforts to slow the drivers of conservation costs and to improve effective spending capacity. For this, the constraints to financial sustainability of biodiversity conservation need to be better understood at country level. Innovative financing mechanisms can be part of the solution and deliver multiple benefits only if their design is carefully fitted to context. Beyond that, landscape approaches to conservation make clear that investing in healthy ecosystems is critical for livelihoods and development.
Keywords: 330